The Effect of PDEODE (Predict-Discuss-Explain-Observe-Discuss-Explain) Strategy On The Concept And Retention Mastery In Nutrition And Health Course On Students With Different Ability - Wulandari, Tabitha Sri Hartati; Amin, Mohamad; Zubaidah, Siti; IAM, Mimien Henie (Sebelas Maret University, 2016)
An indicator of the learning effectiveness could be seen from the studentâs mastery of concepts and whether the concept was long embedded in his memory or the so-called retention. Good retention is one of the factors that will conduct the learning process goes smoothly. The reality shows that the academic ability of each individual is different, and the studentâs mastery of concept and retention are still low, so the selection of strategy is an important factor and learning strategy of PDEODE(Predict-Discuss-Explain-Observe-Discuss-Explain) becomes the choice. The aim of this research is to explain the effect of learning strategy of PDEODE on the mastery of concept and retention in nutrition and health course on students with different academic ability in biology education of PGRI Ronggolawe University, Tuban. This study was a quasi-experimental research and the research design was pretest-posttest control group random subjects. The results of Manova indicated that 1) there was a difference in the mastery of concepts on nutrition and health subject among the students who were taught by PDEODE and conventionally, 2) there was a difference in retention on nutrition and health subject among students who were taught by PDEODE and conventionally, 3) there was a difference of mastery of concepts on nutrition and health subject among the students with the high academic ability and low academic ability, 4) there was a difference of retention on nutrition and health subject among the students with the high academic ability and low academic ability, 5) there was interaction between learning strategy and academic ability on the studentâs mastery of concept on nutrition and health subject, 6) there was interaction between learning strategy and academic ability on the retention of the students on nutrition and health subject.